The social media "magic": Virtually engaging visitors during COVID-19 temporary closures - Brittany Ryder; Tingting Zhang; Nan Hua (Administrative Sciences, 2021)
The purpose of this study was to explore what types of digital content cultural institutions implemented during COVID-19 temporary closures and their effects on social media engagement. Existing research identified the role of digital content and social media in cultural institutions, but only in times of normal operations. This study adds to the existing literature by exploring the types of digital content implemented, impacts on social media engagement, measures of social media engagement, and future implications in regard to COVID-19 temporary closures. This study recruited 66 cultural institutions from across the United States to take part in in-depth semi-structured phone interviews to fulfill the research goals. Museums, zoos, aquariums, performing arts organizations, heritage foundations, and historical societies were represented. A qualitative approach was adopted, and content analysis on the interview transcripts indicated that cultural institutions implemented digital content to build communities through live and serialized content, partnerships, fundraising, increased transparency, and increased accessibility during temporary closures. Using primarily Instagram and Facebook with their digital content, cultural institutions increased social media engagement during this time. Although there was no consensus on best practices in measuring social media engagement, many institutions highlighted tracking active engagement such as likes, comments, and shares. As a result of the success of the digital content, cultural institutions planned continued digital content campaigns such as videos, blogs, partnerships, and paid educational content in times of normal operations.
Keywords: 350; aquariums; content analysis; COVID-19; COVID-19 temporary closures; cultural institutions; interviews; museums; performing arts organizations; social media; social media engagement; zoos